PENINGKATAN PENGETAHUAN DAN SIKAP IBU RUMAH TANGGA TENTANG PENCEGAHAN HIPERTENSI MELALUI MEDIA ALAT PERAGA PAKSA DI KELURAHAN PARAK GADANG TIMUR KOTA PADANG - Marisa Putri, Yolla; Sidiq, Rapitos; Munthe, Sorpiyani; Fitra Hayati, Neni; Maria Silaban, Evi (Jurnal Promosi Kesehatan Poltekkes Bengkulu, 2025)
Background: Hypertension is a disease characterized by blood pressure exceeding 140/90 mmHg. Data from Parak Karakah Community Health Center, Padang City, in 2024 recorded 241 hypertension cases. Purpose: This study aimed to analyze the improvement of mothers’ knowledge and attitudes regarding the prevention of hypertension risk using the PAKSA visual aid in the working area of Parak Karakah Community Health Center, Parak Gadang Timur Subdistrict, Padang City. Methods: This study applied a mixed-method approach conducted from January to May 2025. The qualitative data were obtained through source triangulation using in-depth interviews with housewives, non-communicable disease program holders, a linguist, and a design expert. The quantitative approach employed a quasi-experimental design with a one-group pre-test and post-test, using total sampling of 30 housewives. Data were analyzed univariately to describe variable distribution and bivariately using the Wilcoxon test to examine differences before and after intervention. Results: Qualitative findings revealed that the Paksa visual aid was developed according to the target group’s needs, presenting illustrations of the effects of cigarette smoke on blood vessels and the heart. Quantitative results showed an increase in the median knowledge score from 12.00 to 17.00 and in attitudes from 33.00 to 48.00. The Wilcoxon test indicated a significant difference in knowledge (p=0.0001) and attitudes (p=0.0001) before and after the educational intervention. Conclusion: This study demonstrated an improvement in housewives’ knowledge and attitudes toward hypertension risk prevention. The PAKSA visual aid is expected to be further developed as a preventive health education medium for various diseases across other community groups. Keywords: hypertension, housewives, knowledge, attitude, visual aid